PENGARUH TERPAAN NATIVE ADVERTISING ERIGO TAKE OVER DAN KREDIBILITAS CELEBRITY ENDORSER DI MEDIA SOSIAL TERHADAP BRAND IMAGE ERIGO - Daffa Satriowibowo; Tandiyo Pradekso; Nurist Surayya Ulfa (Interaksi Online, 2022)
Even though Erigo has carried out a massive marketing strategy with a large budget, which is approximately 718 million for native advertising, Erigo take over and 50 billion for celebrity endorsers who have high credibility. This is inversely proportional to the efforts made by Erigo in running native advertising related to the Erigo take over program as a program that is ready to go global and optimize celebrity endorser strategies on social media. This research uses explanatory quantitative research type. The population in this study is an audience aged 18-35 years who have been exposed to native advertising Erigo take over and know Erigo's celebrity endorser. This study uses a non-probability sampling technique with a total of 100 respondents. The sampling technique used in this study was based on chance or accidental. The theory used in this research is cognitive learning theory and source credibility theory. The findings in this study indicate that Erigo's take over native advertising exposure is at a sufficient level. This shows that some respondents have sufficient knowledge of exposure to information in native advertising Erigo take over. Then, exposure to celebrity endorser Erigo's credibility on social media is at a high level. This shows that some respondents have a good perception of the credibility of the celebrity endorser owned by Erigo. Then, most of the respondents also have a good perception of Erigo's brand image. The results of testing all hypotheses in this study using simple linear regression analysis showed that the study was not significant or there was no influence between the X1 variable (Native Advertising Erigo Take Over Exposure) on the Y variable (Erigo Brand Image) with a significance value of 0.941. This shows that the level of exposure to information from native advertising Erigo take over in online media articles does not partially affect Erigo's brand image. Then, there is no or no significant effect between variable X2 (Credibility of Celebrity endorsers on social media) to variable Y (Brand image Erigo) with a significance value of 0.497. this shows that the high and low credibility of celebrity endorser Erigo on social media does not partially affect Erigo's brand image.